Chaucerian Ecopoetics Deconstructing Anthropocentrism in the Canterbury Tales - Normandin, Shawn (The New Middle Ages, 2018)
Chaucerian Ecopoetics performs ecocritical close readings of Geoffrey Chaucer's poetry. Shawn Normandin explains how Chaucer's language demystifies the aesthetic charm of his narratives and calls into question the anthropocentrism they often depict. This text combines ecocriticism with reading techniques associated with deconstruction, to provide innovative interpretations of the General Prologue, the Knight's Tale, the Miller's Tale, the Reeve's Tale, the Franklin's Tale, the Physician's Tale, and the Monk's Tale. In stressing the importance of rhetorical nuance and literary form, Chaucerian Ecopoetics enables readers to better understand the ideological prehistory of today's environmental crisis.